THE ROLE OF DIGITAL TECHNOLOGIES IN THE DEVELOPMENT OF AN INNOVATIVE ECONOMY: https://doi.org/10.5281/zenodo.14535606 - Khalilova, Gulnoza; Rashidov , Abror (Journal of Contemporary World Studies, 2024)
This article analyzes the role and importance of digital technologies in the development of an innovative economy. Innovations such as digital technologies, in particular artificial intelligence, blockchain, Internet of Things (IoT), and Big Data (Big Data), play an important role in digitizing economic systems and making them more efficient. This article will consider the potential and current capabilities of digital technologies in the modernization of the economy.